2017
DOI: 10.7759/cureus.1055
|View full text |Cite
|
Sign up to set email alerts
|

Radiosurgical Ablation of the Renal Nerve in a Porcine Model: A Minimally Invasive Therapeutic Approach to Treat Refractory Hypertension

Abstract: BackgroundHypertension is strongly associated with cardiovascular diseases such as heart failure, stroke, kidney disease, and has been correlated with an increased risk for heart attack. Current treatment regimens for hypertension are highly inadequate, with reports indicating that only 50.1% of the clinical population with the disease has their blood pressure under control.ObjectiveTo study the feasibility of using minimally invasive radiosurgery to ablate the renal nerves as a novel treatment for refractory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Additionally, ablative radiotherapy is used in non-oncologic indications, such as trigeminal neuralgia, arteriovenous malformations, seizures, and psychiatric disorders in the brain, and has been explored for renal artery hypertension, back pain, and cardiac arrhythmias, termed stereotactic arrhythmia radioablation (STAR) [ 8 , 9 ••].…”
Section: Radiotherapy and Stereotactic Ablative Radiotherapy: Generalmentioning
confidence: 99%
“…Additionally, ablative radiotherapy is used in non-oncologic indications, such as trigeminal neuralgia, arteriovenous malformations, seizures, and psychiatric disorders in the brain, and has been explored for renal artery hypertension, back pain, and cardiac arrhythmias, termed stereotactic arrhythmia radioablation (STAR) [ 8 , 9 ••].…”
Section: Radiotherapy and Stereotactic Ablative Radiotherapy: Generalmentioning
confidence: 99%
“…26,27 Non-malignant diseases that may benefit from the therapy are being investigated, including hypertension treated via renal arterial denervation. 28…”
Section: Historical Background To Stereotactic Radioablationmentioning
confidence: 99%
“…High blood pressure is a risky factor for kidney disease, stroke, premature birth, and cardiovascular disease [ 2, 3 ]. High blood pressure is associated with sympathetic nervous system, because increased levels of sympathetic system activity lead to high blood pressure and therapeutic treatments are effective on controlling the sympathetic nervous system and had little success in controlling and treating hypertension [ 4 ]. Researchers have found that the number of adults with high blood pressure has doubled between 1995 and 2005 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, high blood pressure control is considered as an important indicator in assessing the impact of health services [ 2 ]. Studies have shown that only 50.1% of the population with high blood pressure can control their disease (with a level below 140/90 mmHg) [ 4 ]. Factors, such as overweight and obesity, low exercise activities, high alcohol consumption, and the use of drugs and drugs, increase the risk of hypertension in individuals [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation